Management of Microsprinkler Systems for Florida Citrus - Lawrence R. Parsons; Kelly T. Morgan (EDIS, 2004)
Irrigation is an essential part of the Florida citrus production system. In one study, irrigation increased yield by 39 to 64% over the non-irrigated controls. Microsprinkler irrigation systems have become the standard for Florida citrus. Microsprinkler and drip systems have been collectively referred to as trickle, low volume irrigation, or microirrigation systems. Compared to overhead sprinklers, low volume systems can save water if they are properly managed. Because these systems usually operate at lower pressures than conventional overhead systems, there can also be appreciable savings from reduced energy costs. In addition, microsprinkler irrigation can provide partial frost protection for both young and mature trees. This document is HS-958, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date printed: October 2004.